2018
DOI: 10.1016/j.chiabu.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the state of the literature on sexually exploited boys internationally

Abstract: This systematic review assessed the current state of the literature on sexually exploited boys internationally. We aimed to describe what is known about sexual exploitation of boys, identify gaps in the literature, provide implications for practice, and make recommendations for future research. Multiple database searches were conducted using a combination of controlled vocabulary and keywords to capture child and adolescent sexual exploitation. Our search identified 11,099 unique references and excluded studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 39 publications
1
27
0
5
Order By: Relevance
“…The studies confirmed earlier research indicating that boys are an important part of adolescents selling sex, which is often in opposition to the general awareness within society (Kaestle, 2012;McNeal & Walker, 2016;Mossige et al, 2007;Moynihan et al, 2018;Pedersen & Hegna, 2003;Svedin & Priebe, 2007). Further, Study II might help us to understand the gender bias that has been seen in the existing literature regarding adolescents selling sex, where boys are seldom seen in clinical samples (Mitchell et al, 2017;Moynihan et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The studies confirmed earlier research indicating that boys are an important part of adolescents selling sex, which is often in opposition to the general awareness within society (Kaestle, 2012;McNeal & Walker, 2016;Mossige et al, 2007;Moynihan et al, 2018;Pedersen & Hegna, 2003;Svedin & Priebe, 2007). Further, Study II might help us to understand the gender bias that has been seen in the existing literature regarding adolescents selling sex, where boys are seldom seen in clinical samples (Mitchell et al, 2017;Moynihan et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…Hence, the selling of sex among adolescents could often be seen as an independent act where no pimp or adult is involved (Edinburgh et al, 2015;Fredlund et al, 2013;Jonsson et al, 2014). The buyers has been described as both male and female (Fredlund et al, 2013;Lavoie et al, 2010;Moynihan et al, 2018) and in a Swedish interview study, the buyers were described as mostly men but a heterogeneous group in regard to age, occupation and civil status (Jonsson & Svedin, 2012).…”
Section: The Selling Of Sexmentioning
confidence: 99%
See 2 more Smart Citations
“…The sexual abuse of children and adolescents for economic gain, more commonly known as the “commercial sexual exploitation of children” (CSEC) is an atrocious crime (Albanese, 2007; Barnitz, 2001), yet little is known about it. For example, no one knows for certain the extent to which CSEC occurs, who are the perpetrators involved, and how many children are victims (Barnert et al., 2017; Moynihan et al., 2018). No one knows whether programs to address the needs of child victims of commercial sexual exploitation benefit or harm them (Dell et al., 2017; Gerassi, 2017; Goldberg & Moore, 2018).…”
mentioning
confidence: 99%